Alkali-Metal-Mediated Synergistic Effects in Polar Main Group Organometallic Chemistry - Robertson, Stuart D; Uzelac, Marina; Mulvey, Robert E (Chemical reviews, 2019)
The development of synthetic chemistry since the early 1900s owes much to the service of organolithium reagents. Brilliant bases (e.g., deprotonating C-H bonds), nucleophiles (e.g., adding to unsaturated molecules), and transfer agents (e.g., delivering ligands to other metals), these versatile virtuosi and to a lesser extent the organic derivatives of the other common alkali metals sodium and potassium have proved indispensable in both academia and technology. Today these monometallic compounds are still utilized widely in synthetic campaigns, but in recent years they have been joined by an assortment of bimetallic formulations that also contain an alkali metal but in company with another metal. These bimetallic formulations often exhibit unique chemistry that can be interpreted in terms of synergistic effects, for which the alkali metal is essential, though it is often the second metal that performs the synthetic transformation. Here, this "alkali-metal-mediated" chemistry is surveyed focusing mainly on bimetallic formulations containing two alkali metals or an alkali metal paired with magnesium, calcium, zinc, aluminum, or gallium. In this International Year of the Periodic Table (IYPT), we ponder whether a Pairiodic Table of Element Pairs will emerge in the future.